2007
DOI: 10.1139/b07-081
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of anArabidopsisglyoxylate reductase: general biochemical properties and substrate specificity for the recombinant protein, and developmental expression and implications for glyoxylate and succinic semialdehyde metabolism in planta

Abstract: Constitutive expression of an Arabidopsis thaliana (L.) Heynh cDNA (GenBank accession No. AY044183 ) in a succinic semialdehyde (SSA) dehydrogenase-deficient yeast ( Saccharomyces cerevisiae Hansen) mutant enables growth on γ-aminobutyrate and significantly enhances the accumulation of γ-hydroxybutyrate. In this report, the cDNA (designated hereinafter as AtGR1) was functionally expressed in Escherichia coli , and the recombinant protein purified to homogeneity. Kinetic analysis of substrate specificity reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 46 publications
5
61
1
Order By: Relevance
“…This suggests that minor contributions can be made by additional enzymes. In contrast with an earlier report on spinach glyoxylate reductase, which had small activity with hydroxypyruvate (Kleczkowski et al, 1986), two recently identified Arabidopsis glyoxylate reductases, one cytosolic and one plastidial, do not show HPR activity (Hoover et al, 2007;Simpson et al, 2008). More likely candidate enzymes for these minor activities would be other 1-hydroxacid dehydrogenases with relaxed substrate specificity, for example lactate dehydrogenase (Betsche, 1981), or the two putative Arabidopsis proteins At1g12550 and At2g45630.…”
Section: Discussioncontrasting
confidence: 76%
“…This suggests that minor contributions can be made by additional enzymes. In contrast with an earlier report on spinach glyoxylate reductase, which had small activity with hydroxypyruvate (Kleczkowski et al, 1986), two recently identified Arabidopsis glyoxylate reductases, one cytosolic and one plastidial, do not show HPR activity (Hoover et al, 2007;Simpson et al, 2008). More likely candidate enzymes for these minor activities would be other 1-hydroxacid dehydrogenases with relaxed substrate specificity, for example lactate dehydrogenase (Betsche, 1981), or the two putative Arabidopsis proteins At1g12550 and At2g45630.…”
Section: Discussioncontrasting
confidence: 76%
“…GABA may be converted by plant enzymes into ␥-hydroxybutyrate (GHB) with succinic semialdehyde (SSA) as a toxic intermediate (18,19). A nonenzymatic conversion of GHB into ␥-butyrolactone (GBL) may occur at acidic pH.…”
Section: Resultsmentioning
confidence: 99%
“…AY044183) was expressed in a recombinant bacterial system as described elsewhere (Hoover et al 2007). The recombinant protein was purified to homogeneity and enzymatic activity measured continuously as the oxidation of NADPH ((SSA ?…”
Section: Methodsmentioning
confidence: 99%